Simultaneous retrieval of optical and geometrical parameters of multilayered turbid media via state-estimation algorithms - García, Héctor; Baez, Guido; Pomarico, Juan (Biomedical optics express, 2018)
In the present paper we propose an implementation of the Kalman filter algorithm, which allows simultaneous recovery of the absorption coefficient, the reduced scattering coefficient and the thicknesses of multi-layered turbid media, with the deepest layer taken as semi-infinite. The approach is validated by both Monte Carlo simulations and experiments, showing good results in structures made up of four layers. As it is a Bayesian algorithm, prior knowledge can be included to improve the accuracy of the retrieved unknowns. One of the most promising applications of this approach is the capability of real-time monitoring of living organs by near infrared spectroscopy. In particular, determination of blood perfusion in the adult head is one of the desired goals, allowing continuous control of stroke patients. This demands accurate measurement of the optical properties, especially absorption, of the head layers, from scalp to the cortex.